Innovation Adoption and Resistance of Functional Postbiotics: Consumer Intentions for Sleep and Mental Wellbeing - Piyapinyo, Chawin; Assarut, Nuttapol; Borompichaichartkul, Chaleeda (Ital Publication, 2025)
This study investigates the key factors influencing consumer purchase intention toward functional postbiotic beverages designed to enhance sleep quality and mental health. It focuses on perceived innovation characteristics (PIC), innovation resistance (IR), attitude, and the moderating role of product knowledge. Data were collected through a structured questionnaire from 400 health-conscious Thai consumers aged 18–65 with prior experience in functional foods. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the relationships among PIC, IR, attitude, and purchase intention, including the moderating effect of product knowledge. The findings reveal that relative advantage, compatibility, and attitude positively influence purchase intention, while the claim skepticism barrier has a negative impact. Complexity and trialability were found to be non-significant. Additionally, compatibility significantly influences attitudes across high- and low-product-knowledge consumers. However, product knowledge did not moderate the direct relationship between PIC and purchase intention. Attitude emerged as a key mediator. This study contributes to innovation adoption theory by highlighting the roles of compatibility and attitude while introducing trust and claim skepticism as critical resistance factors. It offers actionable implications for marketers aiming to enhance consumer trust and align products with daily routines.